2022
DOI: 10.1115/1.4053393
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of a Separated Electric Compound Spark-Ignition Engine for Hybrid Vehicle Application

Abstract: In-cylinder expansion of internal combustion engines based on Diesel or Otto cycles cannot be completely brought down to ambient pressure, causing a 20% theoretical energy loss. Several systems have been implemented to recover and use this energy such as turbocharging, turbo-mechanical and turbo-electrical compounding, or the implementation of Miller Cycles. In all these cases however, the amount of energy recovered is limited allowing the engine to reach an overall efficiency incremental improvement between 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…At present, the IC engines have the highest efficiency of 45~50%, with the peak power density and energy density between 1000~1500 W/kg and 1320~5000 W•h/kg [11]. Other disadvantages include the complex transmission system, which generates a lot of noise during the normal operation process [12].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the IC engines have the highest efficiency of 45~50%, with the peak power density and energy density between 1000~1500 W/kg and 1320~5000 W•h/kg [11]. Other disadvantages include the complex transmission system, which generates a lot of noise during the normal operation process [12].…”
Section: Introductionmentioning
confidence: 99%
“…These values are higher than the efficiency of turbines commonly used for turbocharging, on account of the more favorable working condition already mentioned, which allows a design strategy for the best efficiency under steady operation, and also permits the electric generator to control the turbine speed of rotation, maximizing its efficiency, apart from the power produced. Some preliminary evaluations made by the same authors [2][3][4] showed that the separated electric compound engine has good potential, since vehicle fuel economy increments up to 15% may be obtained in comparison to a reference hybrid propulsion system endowed with a traditional turbocharged engine with equal maximum output power (73.5 kW). It was also found that the turbo-generator could contribute to vehicle traction by about 34% of the overall power generated for the propulsion, with a maximum delivered power of about 20 kW.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the rotational speed of the turbine is independent from the engine and from the compressor, it can be optimally controlled and set to the best value acting through the connected generator. In their preliminary studies [13,14], the authors demonstrated that this system is very promising, as it may achieve overall vehicle efficiency advantages up to 15% with respect to a reference hybrid propulsion system of the same nominal overall output power (73.5 kW) equipped with a traditional turbocharged engine. Furthermore, the authors showed that the contribution of the turbogenerator may reach an impressive 33.9% share of the total power generated by the whole system, with maximum power delivered of 20 kW; in this regard, it must be pointed out that in their previous works, the exhaust gas turbine considered was supposed to be optimized for steady-state operation, since in a hybrid propulsion system the thermal engine undergoes small speed and load variations.…”
Section: Introductionmentioning
confidence: 99%
“…These values are substantially higher than the efficiency of a common turbocharging turbine on account of the more favourable working condition already mentioned, which allows a design strategy aimed at maximizing the efficiency in steady operation, and also permits the control module of the electric generator to operate the turbine at its best efficiency speed ratio, regardless of the power produced. It is also worth noting that in the preliminary evaluations performed [13,14], the efficiency of the electric motor (0.90) employed to drive the supercharger was considered in the evaluation of the power drained by the compressor, since it constitutes an ancillary device, which burdens the overall energy balance of the engine; instead, concerning the turbine, the efficiencies of the electric generator and of the battery charging were not considered coherently with the approach followed for the main thermal engine, whose power output was not reduced by generator efficiency or by battery-charging efficiency; the reason for this approach is that the engine power split (i.e., part to the generator and part to the wheels) should depend on the particular mechanical transmission adopted and was not defined in the evaluation carried out. Moreover, both the generator and the battery-charging efficiency can also be considered the same for the comparative hybrid propulsion system equipped with the traditional turbocharged engine; on account of this, the authors decided to fairly base the comparison on the overall mechanical output power produced.…”
Section: Introductionmentioning
confidence: 99%